Thrombophilia and retinal vascular occlusion - Glueck, Charles J (Dove Medical Press, 2012)
PURPOSE: The purpose of this research was to assess associations of thrombophilia with central retinal vein occlusion (CRVO), central retinal artery occlusion (CRAO), and amaurosis fugax (AF); to evaluate outcomes of normalizing high homocysteine; and to study CRVO, CRAO, and AF developing in estrogens/estrogen agonists in women subsequently shown to have thrombophilia. METHODS: Measures of thrombophilia–hypofibrinolysis were obtained in 132 CRVO cases, 15 CRAO cases, and 17 AF cases. Cases were compared to 105 healthy control subjects who did not differ by race or sex and were free of any ophthalmologic disorders. All cardiovascular disease (CVD) risk factors were compared to healthy general populations. MAIN OUTCOME MEASURES: The main outcome measure of this study was thrombophilia. RESULTS: CRVO cases were more likely than controls to have high homocysteine (odds ratio [OR] 8.64, 95% confidence intervals [CI]: 1.96–38), high anticardiolipin immunoglobulin M (IgM; OR 6.26, 95% CI: 1.4–28.2), and high Factor VIII (OR 2.47, 95% CI: 1.31–7.9). CRAO-AF cases were more likely than controls to have high homocysteine (OR 14, 95% CI: 2.7–71.6) or the lupus anticoagulant (OR 4.1, 95% CI: 1.3–13.2). In four of 77 women with CRVO (two found to have high homocysteine, two with inherited high Factor XI), CRVO occurred after starting estrogen–progestins, estrogen–testosterone, or estrogen agonists. In one of eight women with CRAO found to have high anticardiolipin antibody IgG, CRAO occurred after starting conjugated estrogens, and AF occurred after starting conjugated estrogens in one of eleven women with AF (inherited protein S deficiency). Therapy for medians of 21 months (CRVO) and 6 months (CRAO-AF) was 5 mg folic acid, 100 mg B6, and 2000 mcg/day B12 normalized homocysteine in 13 of 16 (81%) CRVO cases and all five CRAO-AF cases with pretreatment hyperhomocysteinemia. The CRVO cases had an excess of hypertension; CRAO-AF cases had an excess of type 2 diabetes and hypertension. CONCLUSION: Treatable thrombophilia, hyperhomocysteinemia in particular, is more common in RVO cases than in normal controls. RVO occurs after estrogens or estrogen agonists were administered in women subsequently shown to have thrombophilia.